Fuzzy adaptive event‐triggered control of high‐power nonlinear systems with fixed‐time convergence. (16th September 2022) - Yang, Tingting; Kang, Haobo; Ma, Hongjun
Summary: This article investigates the adaptive fuzzy event‐triggered practical fixed‐time control for a class of non‐strict feedback high‐power nonlinear systems with completely unknown function. Compared with similar results, the system model considered here is more general, including powers equal to 1 and this article relaxes the restrictions of nonlinear functions. As we all know, high‐power systems have the uncontrollable ability in the process of linearization, so that successfully presented for standard (low‐order) nonlinear systems may fail to work. In the adding one power integrator framework, this article overcomes the difficulty of control design caused by the powers of control input and the relative threshold event‐triggered signal is introduced to reduce the unnecessary waste of communication resources. Then, an adaptive fuzzy event‐triggered controller is designed via backstepping technique, which can ensure that all the closed‐loop signals are practical fixed‐time stability. Finally, numerical simulation and practical example are provided to validate the effectiveness of the presented control algorithm.